New iterative method for solving gas dynamic equation - Hemeda, Aatef; Saleh Alluhaibi, Mohamed (International Journal of Applied Mathematical Research, 2014)
In this paper, the gas dynamic equation is solved through new iterative method (NIM). The obtained results are compared with those of homotopy perturbation method (HPM), variational iteration method with He's polynomials (VIMHP) and Laplace transform new homotopy perturbation method (LTNHPM). It is noted that the NIM in case of nonhomogeneous problems takes the form of a convergent series with easily computable components. This method is able to solve large class of linear and nonlinear equations effectively, more easily and accurately; and thus the method has been widely applicable to solve any class of equations in sciences and engineering. Keywords: New Iterative Method, Homotopy Perturbation Method, Variational Iteration Method with He's Polynomials, Laplace Transform New Homotopy Perturbation Method, Gas Dynamic Equation.